2006
DOI: 10.1103/physrevlett.96.097001
|View full text |Cite
|
Sign up to set email alerts
|

Raising Bi-O Bands above the Fermi Energy Level of Hole-DopedBi2Sr2CaCu2O8+δand Other Cuprate Superconductors

Abstract: The Fermi surface (FS) of Bi2Sr2CaCu2O 8+δ (Bi2212) predicted by band theory displays Birelated pockets around the (π, 0) point, which have never been observed experimentally. We show that when the effects of hole doping either by substituting Pb for Bi or by adding excess O in Bi2212 are included, the Bi-O bands are lifted above the Fermi energy (EF ) and the resulting first-principles FS is in remarkable accord with measurements. With decreasing hole-doping the Bi-O bands drop below EF and the system self-do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 24 publications
(23 reference statements)
10
36
0
1
Order By: Relevance
“…This choice is also supported by calculations of Ref. 25, which show the sensitivity of the position of the Bi-band with respect to impurities and doping. The absence of the bottom of the BiO band in the STS spectra may also be due to a voltage gradient across the insulating filter layers (BiO and SrO layers) when applying a bias voltage between the tip and the sample.…”
Section: B Construction Of the Uncorrelated Normal State Hamiltoniansupporting
confidence: 58%
See 1 more Smart Citation
“…This choice is also supported by calculations of Ref. 25, which show the sensitivity of the position of the Bi-band with respect to impurities and doping. The absence of the bottom of the BiO band in the STS spectra may also be due to a voltage gradient across the insulating filter layers (BiO and SrO layers) when applying a bias voltage between the tip and the sample.…”
Section: B Construction Of the Uncorrelated Normal State Hamiltoniansupporting
confidence: 58%
“…While the tight-binding band structure is in reasonable agreement with the LDA band structure of Ref. 25, in order to carry out spectroscopic computations, one must additionally make sure that the underlying wavefunctions are described correctly including their symmetries. Our procedure based on the the use of Koster-Slater matrix elements not only fits the band stuctures, but the symmetries and phases of the associated wavefunctions are also described correctly.…”
Section: B Construction Of the Uncorrelated Normal State Hamiltoniansupporting
confidence: 52%
“…Singh and Pickett ͑1995͒ found that in Bi2201 the calculated Bi-O bands move upward by ϳ400 meV when the distortion of the BiO planes is taken into account. Very recently, Lin et al ͑2006͒ found that a similar shift occurs in Bi2212 when lead or oxygen doping is introduced in the calculation.…”
Section: Role Of the Bio Surface Layermentioning
confidence: 72%
“…The highest T c is about 130 K for cuprate superconductors close to the range. From the Fig.4, there are larger vertex corrections at higher Ω P and larger λ, however the T c doesn't changes significantly because the band-width of CuO 2 plane for cuprate superconductors such as Bi2212 is not too small about 4 eV, and the Fermi-energy E F is at least 1 eV [29,30].…”
Section: Discussion and Summarymentioning
confidence: 94%